The General Interregional Price Model - Chris Jensen-Butler; Bjarne Madsen (European Regional Science Association (ERSA), 2006)
In the input-output tradition regional and interregional spill-over and feedback effects are related to changes in the real economic activities. However, the effects of changes in costs and prices on real economic activity have usually been neglected, despite the fact that the redistributive effects from this dual element in the intra- and interregional economy might be considerable and have effects on economic activity, which are comparable with the quantity effects. CGE-models on the other hand have explicitly addressed this issue using non-linear functions to overcome theoretical problems related to the use of fixed coeffients, permitting for example a more satisfactory treatment of substitution between factors of production or commodities as well as the effects of changing costs on patterns of trade and other forms of interaction. Following the input-output tradition, a structural model for the formation of prices in a local economy involving the price determination through local economic interaction such as commuting and shopping an interregional interaction, such as trade the general interregional price model is derived. The equations of the general interregional price model are presented together with the solution of the model. The theoretical changes examined include a set of new geographical concepts and in the context of an interregional SAM the development of the two-by-two-by-two approach, involving two sets of actors (production units and institutional units), two types of markets (commodities and factors) and two locations (origin and destination). Finally, a simultaneous solution to the combined general interregional quantity and price model based upon the most simple link is outlined.
Keywords: 330